CHARACTER BUILDING OF STUDENTS THROUGH CANTEEN SERVICES AT SDN SLENDRO 1 - Muhammad Erikko Abimayu; M. Amirul Ramli; Dina Mayadiana Suwarma (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
This research aims to find out how character is formed through canteen services at SDN Slendro 1. This research uses a qualitative descriptive research type because this research only describes and describes the character of students who are formed through the canteen. Data sources were obtained from canteen keepers, high school teachers, and school principals. The data collection methods used in this research are observation, interviews and data analysis techniques carried out by means of data reduction, data presentation and drawing conclusions from research results. The conclusion of this research shows that 90% of students at SDN Slendro 1 have succeeded in forming character through canteen services. This is proven by the formation of a disciplined character that can be seen when it is not break time, the canteen guard will not serve students who want to buy food or drinks in the canteen, apart from that, the honest character is also applied when paying in the canteen. Students are orderly queuing to pay and no one takes it. without paying even though they have to wait, another character that is formed is responsibility which can be seen by students obeying the existing rules, namely by not forcing them to buy food or drinks when it is not break time.